A Microfacet‐based Hair Scattering Model. (30th July 2022) - Huang, W.; Hullin, M. B.; Hanika, J.
Abstract: The development of scattering models and rendering algorithms for human hair remains an important area of research in computer graphics. Virtually all available models for scattering off hair or fur fibers are based on separable lobes, which bring practical advantages in importance sampling, but do not represent physically‐plausible microgeometry. In this paper, we contribute the first microfacet‐based hair scattering model. Based on a rough cylinder geometry with tilted cuticle scales, our far‐field model is non‐separable by nature, yet allows accurate importance sampling. Additional benefits include support for elliptical hair cross‐sections and an analytical solution for the reflected lobe using the GGX distribution. We show that our model captures glint‐like forward scattering features in the R lobe that have been observed before but not properly explained.